TAMAN TAMAN BACA MASYARAKAT (TBM) SAHITYA SEBAGAI UPAYA MEMBANGUN BUDAYA LITERASI DI DESA CANDALI - Muhammad Aras Prabowo; Hidayani Hidayani; Defita Rahma; Silvi Aulia (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2023)
Community Reading Park is a non-formal education as a follow-up to government programs and continuing education in empowering the community through the literacy movement. Community Reading Park is a program to build an educational village from the Indonesian Nahdlatul Ulama University as an implementation of one of the Tri Dharma of Higher Education, namely community service. The method used is active participation, namely; (1) Observation and Planning (3) Implementation of TBM establishment and training of tutors for TBM managers (4) Evaluation (5) Follow-up. The results of the observation found that many children dropped out of school in Candali Village. TBM as a library and alternative education in empowering the community and fostering interest in reading in the Candali Village community. The outcome of the Community Service program is sustainable TBM, continued by local youth who have been equipped with the skills and management to manage TBM. The Unusia Community Service Team is still monitoring the development of TBM through the manager's WhatsApp group.